Implications of Automation and Artificial Intelligence for Employment Law Politics - Firman Nurdiyansyah Sunandar; Andri Herman Setiawan; Ahmad Juaeni; Johannes Triestanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the implications of automation and artificial intelligence (AI) on employment law politics in Indonesia, as well as their impact on employment structures and relationships. Along with rapid technological advances, especially in the fields of automation and AI, the world of employment is undergoing significant transformations that affect work models, employment contract arrangements, and worker protection. This study will identify how these technologies affect employment relationships, creating new opportunities, but also threatening the sustainability of jobs in certain sectors. This study uses a qualitative approach with descriptive analysis to understand the dynamics of change resulting from automation and AI, and their legal implications for workers and companies. The main focus of this study is to assess the extent to which employment policies in Indonesia can accommodate the new challenges arising from this technological shift, and how the existing employment law system needs to adapt to remain relevant and effective. The findings of this study are expected to contribute to policymakers, legal practitioners, and academics, by providing recommendations on how employment policies in Indonesia can be updated to anticipate the negative impacts of technology, protect workers' rights, and create social justice in an increasingly digitalized world of work. This research will also provide an overview of the role of technology in shaping future industrial relations and regulations, and propose a legal framework that is adaptive to the development of automation and artificial intelligence in Indonesia.